Antioxidant activity of Galium mollugo L. extracts obtained by different recovery techniques - Milić Petar S.; Stanojević Ljiljana P.; Rajković Katarina M.; Milić Slavica M.; Nikolić Vesna D.; Nikolić Ljubiša B.; Veljković Vlada B. (Hemijska Industrija, 2013)
The yield of extractive substances, antioxidant activity, as well as total phenolic and total flavonoid contents of aqueous-ethanolic extracts obtained from aerial parts of Galium mollugo L. by different extraction techniques (maceration, reflux and ultrasonic extraction) were reported. The antioxidant activity of extracts was tested by measuring their ability to scavenge a stable DPPH free radical, while the total phenolic and total flavonoid contents were determined according to the Folin-Ciocalteu procedure and a colorimetric method, respectively. The Duncan’s multiple range tests were used to evaluate if there were significant differences among yields of extractive substances, total phenolics, total flavonoids and EC50 values for the extracts obtained by different extraction techniques. The extracts obtained by the reflux extraction contained higher amounts of extractive substances, as well as phenolic and flavonoid compounds, and showed a better antioxidant activity than those obtained by the two other recovering techniques.